Using assessment strategically to gestate a student thesis: learning through community - Grant, Carolyn Callie (South African Journal of Higher Education, 2016)
In the context of Higher Education in South Africa and drawing on my experience as a lecturer in two higher education institutions, this article presents my attempts to bring together - and into balance – teaching, supervision and research in an endeavour to offer a transformative learning experience for my post graduate students. It does this by foregrounding student assessment in the M Ed (ELM) degree where the development of a half thesis, underpinned by research, stands as the evidence of success. The article suggests that the M Ed (ELM) degree be conceptualised differently in order that the half thesis be permitted to gestate over a two-year period. Within this conceptualisation, it argues that inspired teaching and meaningful research is best attained through a community of learning approach which seeks to foreground participatory learning, the advancement of scholarly discourse and the development of student agency. Through the use of a case study, the article provides evidence to suggest that a range of authentic assessment strategies which are purposeful and in alignment with the teaching strategies, the content and the intended outcomes of the qualification being taught are essential. It further argues that well-crafted, formative, recursive and sustainable feedback is an essential part of the gestation process.